It Must Be Told: Stories of Hope, Dreams, and Possibility from The Open Book (Oral Histories from the NYC Adult Literacy Community) - Dianne Ramdeholl (Adult Education Research Conference, 2007)
This study chronicled the history of The Open Book, a community based organization in NYC. In this oral history project, the co-constructors of this story analyze the successes and struggles of a grassroots literacy program through the lens of critical theory/liberatory education.